Heat‐killed Mycolicibacterium aurum Aogashima: An environmental nonpathogenic actinobacteria under development as a safe novel food ingredient. Issue 9 (21st July 2021) - Nouioui, Imen; Dye, Timothy
Abstract: Over the last few decades, a wealth of evidence has formed the basis for "the Old Friends hypothesis" suggesting that, in contrast to the past, increasingly people are living in environments with limited and less diverse microbial exposure, with potential consequences for their health. Hence, including safe live or heat‐killed microbes in the diet may be beneficial in promoting and maintaining human health. In order to assess the safety of microbes beyond the current use of standardized cultures and probiotic supplements, new approaches are being developed. Here, we present evidence for the safety of heat‐killed Mycolicibacterium aurum Aogashima as a novel food, utilizing the decision tree approach developed by Pariza and colleagues (2015). We provide evidence that the genome of M. aurum Aogashima is free of (1) genetic elements associated with pathogenicity or toxigenicity, (2) transferable antibiotic resistance gene DNA, and (3) genes coding for antibiotics used in human or veterinary medicine. Moreover, a 90‐day oral toxicity study in rats showed that (4) the no observed adverse effect level (NOAEL) was the highest concentration tested, namely 2000 μ g/kg BW/day. We conclude that oral consumption of heat‐killed M . aurum Aogashima is safe and warrants further evaluation as a novel food ingredient. Abstract : blurb for etocThere is growing realization of the health benefits of restoring human exposure to a more diverse range of microbes than we experience in increasingly urbanized lifestyles. In addition to probiotics, other environmental nonpathogenic organisms, such as environmental saprophytic nontuberculous (NTB) mycobacteria species, were once commonly present in the human diet. Here, we present evidence for the safety of heat‐killed Mycolicibacterium aurum Aogashima as a novel food, utilizing the decision tree approach developed by Pariza and colleagues (2015).